Biodiversity research of darkling beetles on Socotra Island. Part I. The genus Deretus Gahan, 1900 (Coleoptera: Tenebrionidae) - Purchart, Luboš (Zootaxa, 2012)
As a result of biodiversity research on Socotra Island, four new species of the genus Deretus Gahan, 1900 are described—D. bezdeki sp. nov., D. hulai sp. nov., D. necopinatus sp. nov. and D. maderai sp. nov. Deretus wraniki Schawaller, 2004 is synonymised with Deretus denticollis Gahan, 1900. All known species are figured, keyed, and information about their biology and distribution is given.